Pemanfaatan Barang Bekas Sebagai Media Pembelajaran Sekolah Dasar - Dini Apriliani (Program Studi PGSD STKIP PGRI Banjarmasin, 2021)
Abstract: The use of media in the learning process can arouse motivational desires and stimuli of learning activities, even bring psychological influences to students, especially elementary-age students. The use of learning media will help the effectiveness of the learning process and the delivery of messages and content of learning. Learning media is useful to clarify teaching materials, overcome space and time, encourage children to be more active, and can improve cooperation. The benefits of using a learning media will be felt optimally if the teacher is able to choose and use the media in accordance with its purpose and function. Media puzzle made of unused cardboard is one of the many media that can be obtained from the surrounding environment that is useful for learning. In addition, it is useful for students learning media is also useful for educators. Educators will also get the leadership to design learning media, create and maintain media facilities and infrastructure of learning media well.